People's response to disasters in the Philippines vulnerability, capacities, and resilience - Gaillard, J. C.
"Examines the root causes of people's vulnerability, capacities, and resilience in facing a wide range of different hazards. Gaillard examines people's resilience in the aftermath of disasters, with a particular analysis of traditional societies and urban communities and the role of government policies, notably resettlement through geographical relocation. Gaillard successively addresses the roles of the structural features of the Philippine society, individuals' risk perception, and the nature of people's livelihoods. He underscores the Filipinos' capacities to face natural hazards and disasters and suggests ways forward for integrating such capacities, including those of the most marginalized groups, in activities intended to prevent and cope with disasters"--Provided by publisher.